Jonah's whale - Spinelli, Eileen; Ferri, Giuliano (Grand Rapids, MI : Eerdmans Books for Young Readers, 2012)
A contented whale one day sees a ship tossed on the waves by a storm and obeys God's command to save a drowning man by swallowing him.
Keywords: Whales -- Fiction; Jonah -- (Biblical prophet) -- Fiction; Jonah -- (Biblical prophet) -- Juvenile fiction; Whales -- Juvenile fiction; Whales -- Fiction; Jonah -- (Biblical prophet) -- Fiction; Picture books for children